PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN CHEESE WORKS DI GIANYAR - I Nyoman Keramas; I Wayan Mendra (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2019)
The purpose of this study was to determine the effect of job satisfaction and organizational commitment on employee performance at Cheese Worksin Gianyar with a sample of 41 people. Based on the regression analysis shows the positive influence of the job satisfaction independent variable (X1) on the employee performance dependent variable (Y) and the positive influence of the organizational commitment independent variable (X2) on the employee performance dependent variable (Y). From the multiple correlation analysis obtained R value of 0.941 which lies between 0.80-1,000, which means the relationship between job satisfaction, and organizational commitment to employee performance is very strong. From the determination results obtained adjusted R square determination coefficient of 87.9%, which means the influence of job satisfaction and organizational commitment to employee performance by 87.9%. From the results of the t test for job satisfaction variables obtained tcount 3,501 with a significance level of 0.001, this means that statistically job satisfaction has a positive and significant effect on employee performance, so that the first hypothesis can be accepted. For work organization commitment variable obtained tcount 4.663 with a significance level of 0.000 this means thatstatistically organizational commitment has a positive and significant effect on employee performance, so that the second hypothesis can be accepted.